Innovative technology of thermoelectric generator for waste heat recovery in automotive application - Huang, Kuo (2019)
This research project aims to provide an in-depth understanding on waste heat recovery (WHR) technologies for vehicles, especially the thermoelectric generator (TEG) system. Thermoelectric (TE) devices convert the temperature difference between both sides directly into electric potential difference, thus provide electrical power for external load. Because they have advantages of compact package, no mechanical moving parts and high reliability, TE devices are normally applied in WHR for various situation. Based on previous researches, the low in heat transfer efficiency and insufficient in space utilisation of automotive TEG system are the main reasons that prevent the TEG system from massive utilisation in WHR for automotive. Therefore, in these presented works, a novel designed structure for automotive TEG system is promoted, regarding to these issues. The novel TEG system is design in concentric cylindrical structure, which perfectly accords with the shape of the exhaust pipe in vehicle, thus improve the space utilisation of TEG system. Moreover, an efficient heat-transfer device, heat pipe, is employed in this concentric cylindrical TEG system for enhancing heat transfer performance. A heat pipe combines the principles of both thermal conductivity and phase transition to effectively transfer heat between two interfaces, thus has an effective thermal conductivity could approach 100 kW/(m⋅K), in comparison with approximately 0.4 kW/(m⋅K) for copper. By introducing heat pipes into TEG system, the heat transfer between exhaust gas and heat exchanger could be significantly enhanced. In this thesis, the thermal performance of concentric cylindrical TEG system is investigated both numerically and experimentally. The investigation on thermal performance separates in two direction: conductive heat transfer and convective heat transfer. Three-dimensional models for annular thermoelectric module (TEM) and single annular TE unit in concentric cylindrical TEG system is established, in order to simulate the conductive heat transfer of this system in COMSOL Multiphysics. The performance comparison between annular TEM and traditional square TEM is conducted with these three-dimensional models. A proof-concept test rig is built up for verifying the feasibility of heat pipe combined heat exchanger and exploring the influence of different arrangement. In addition, the simulation of a two-dimensional model for cross section of heat exchanger is performed in COMSOL Multiphysics as well, with the aim of inspecting the convective heat transfer within concentric cylindrical TEG system. Four optimized heat exchanger structures with fins or different heat pipe length are designed and compare in the simulation. By compared several structures, a general guidance for designing the heat exchanger for concentric cylindrical TEG system is summarised. Besides the investigation on thermal performance, the system-level of concentric cylindrical TEG system, especially the fuel economy improvement, is studied in this thesis as well. Fuel economy improvement is an important indicator to measure the performance of automotive TEG systems. One-dimensional model of vehicle, engine and TEG system is established in GT-Suite and their performances are simulated consequently. The standardized driving cycle, Worldwide Harmonised Light Vehicles Test Procedure (WLTP), is utilised during the simulation to get a relatively accurate result for fuel economy improvement. In addition, the experimental data obtained from engine test rig of cooperating car manufacture is set as reference data for the fuel consumption model. Based on the calculation of fuel consumption model, a method to improve efficiency of automotive TEG system is introduced by utilising phase change material (PCM) as the thermal energy storage for the system. PCM system could deposit the extra thermal energy during vehicle acceleration and release those energy while vehicle deceleration. Pentaerythritol (PE) is selected as a potential PCM for automotive TEG system with its suitable thermal properties and investigated in this thesis. A test rig for inspecting the feasibility of integrating PCM with TE devices is built up and the experiment is conducted with single TEM with PE. Furthermore, in order to improve thermal conductivity of PE, three different containers with volume ratio at 50 %, 65 % and 80 % are tested experimentally.